WINNING THE BATTLE - A SUCCESS STORY OF MANAGING GENDER DYSPHORIA - Yousafzai, Abdul Wahab; Ayesha Tariq; Nida Bangash (Journal of Ayub Medical College Abbottabad, 2022)
The DSM 5 defines Gender Dysphoria (GD) as a marked incongruence between one’s biological gender and experienced gender. Individuals with GD face increased discrimination in the form of decreased job opportunities, healthcare facilities and increased violence. The definitive treatment for GD is sex reassignment surgery (SRS). The case we present follows a 24-year-old biological male, self-identifying as a female. His experience seeking treatment made him a target for misdiagnoses and mistreatment by healthcare professionals (including psychiatrists, endocrinologists and plastic surgeons) and family resulting in mental agony. After struggling for a long time, he was able to move abroad for SRS. Upon her return to Pakistan as a female she presented as being finally content with her gender and life. The article places emphasis on creating inclusive healthcare plans for individuals with GD and raising awareness among healthcare professional and general population regarding the issue.